2015
DOI: 10.1088/0957-4484/26/10/105706
|View full text |Cite
|
Sign up to set email alerts
|

Morphology dependent field emission of acid-spun carbon nanotube fibers

Abstract: Acid spun carbon nanotube (CNT) fibers were investigated for their field emission properties and performance was determined to be dependent on fiber morphology. The fibers were fabricated by wet-spinning of pre-made CNTs. Fiber morphology was controlled by a fabrication method and processing conditions, as well as purity, size, and type of the CNT starting material. The internal fiber structure consisted of CNT fibrils held together by van der Waals forces. Alignment and packing density of the CNTs affects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The above mentioned flash and plasma observed at the larger applied field at d = 1.25 mm may have destroyed some of the sharper features on the CNT fiber, leaving CNTs with lower field enhancement factors. As observed previously, 14 after the plasma forms at the fiber tip, the fiber tip "plumes" out, thus the field enhancement factor decreases because the fiber tip is less pointy. This would also explain the increased turn-on voltage for FE the last run at d = 1 mm (Fig.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…The above mentioned flash and plasma observed at the larger applied field at d = 1.25 mm may have destroyed some of the sharper features on the CNT fiber, leaving CNTs with lower field enhancement factors. As observed previously, 14 after the plasma forms at the fiber tip, the fiber tip "plumes" out, thus the field enhancement factor decreases because the fiber tip is less pointy. This would also explain the increased turn-on voltage for FE the last run at d = 1 mm (Fig.…”
supporting
confidence: 70%
“…Zhang 2017) where the resistance of the substrate R substrate and of external circuit R ext are negligible since the stainless steel substrate and electrodes are highly conductive (with resistivity of 7.2 × 10 7 Ωm), 34 the resistance of the CNT fiber R CNT fiber = ρ CNT fiber h/πr 2 = 112 Ω, with the assumption of CNT fiber's resistivity 14 being ρ CNT fiber = 1.75 × 10 6 Ωm, length h = 5 mm, and radius r = 5µm, and R contact is the contact resistance between the CNT fiber and the substrate. Therefore, the dominate component of the series resistance in Eq.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…CNT yarns/fibers, as one of the most promising CNT assemblies, have attracted extensive attention. Field emission properties from vertical configuration of yarns/fibers, using various fabrication methods, have been investigated (Wei et al, 2008;Chen et al, 2009;Jang et al, 2010;Hojati-Talemi et al, 2013;Fairchild et al, 2015). A study of field emission from the side of CNT yarn showed a similar performance to the tip of yarn induced in a scanning electron microscope, demonstrating that the field emission from lateral configuration is promising as well (Jang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The fibers were fabricated using a wet spinning technique described by Behabtu et al [8]. This fabrication process ensures that the CNTs comprising the fibers are closely packed and highly aligned which ensures high electrical and thermal conductivity [9] as well as optimal performance when used as eiher wire conductors or field emission cathodes [8,[10][11][12]. Carbon nanotube yarns are made by twisting or braiding together multiple CNT fibers.…”
Section: Samples and Experimentalmentioning
confidence: 99%